PERANAN KEPEMIMPINAN PEREMPUAN DALAM JABATAN PUBLIK (STUDI PADA KANTOR SEKRETARIAT DAERAH KABUPATEN MINAHASA SELATAN) (JURNAL ADMINISTRASI PUBLIK, 2017)
Issues or womenâ€™s issues always interesting to demand, even today more and more scientists or researchers focused more on the assesment of women in particular. It is certainly not in spite of the complexity of the issues relating to women themselves, where there had been no agreement on â€œHow the actual existence of the women is placedâ€. General overview of the Leadership Role of Women in Public Office can be found at area South Minahasa, especially at the District Secretariat Office South Minahasa. The purpose of this study was to determine how the Leadership Role of Women in Public Office. The research method used is a qualitative method. Research on District Secretariat Office South Minahasa shows that the role of womenâ€™s leadership has gone well. Women leaders have been very involved in the activities of the organization in the respective fields of the existing. In program planning and activities of women leaders has been very active. Women leaders always give ideas of programs and activities and always give opinions for ease in planning programs and activities.Keywords : Leadership, Woman, Public Office